The reaching movement in breast cancer survivors: Attention to the principles of rehabilitation. Issue 4 (October 2020) - Teresa, Paolucci; Capobianco, Serena Vincenza; Bai, Arianna Valeria; Adriana, Bonifacino; Francesco, Agostini; Andrea, Bernetti; Marco, Paoloni; Arianna, Cruciani; Valter, Santilli; Luca, Padua; Massimiliano, Mangone
Abstract: Introduction: Breast-cancer is leading cause of morbidity and mortality in women. The prognosis and survival rate of women with breast-cancer have significantly improved worldwide; more attention needs to be paid to rehabilitative interventions after surgery. This paper describes use of reaching movement to assess upper limb motorcontrol and functional ability after breast-cancer surgery (BC). Material and methods: We conducted a cross-sectional observational study consisting of biomechanical evaluation of upper limb limitations in women BC, versus a controlgroup (CG). Thirty breast-cancer survivors and thirty healthy women participated in this study. Both groups were subjected to clinical evaluation of the shoulder joint ROM on the operated side, as an assessment of the muscular-strength of the shoulder with the MRC-scale. The Functional-Assessment was evaluated by the DASH and Constant-Murley-Score. The EORTC QLQ-C30 and VAS were used to measure the quality of life assessment and pain respectively. A Biomechanical evaluation was performed, using Reaching-Task and Surface-EMG. Results: Normal Jerk for BC was higher than CG. Target approaching velocity and movement duration BC was lower than CG. Synergy Anterior Deltoid/Triceps Brachii muscles in CG was higher than BC.